How Having a Clear Why Can Help Us Cope With Almost Anything: Meaningful Well-Being and the COVID-19 Pandemic in México - Quiroga-Garza, Angelica; Cepeda-Lopez, Ana C.; Villarreal Zambrano, Sofía; Villalobos-Daniel, Victor E.; Carreno, David F.; Eisenbeck, Nikolett (Frontiers in Psychology, 2021)
Background. Coronavirus disease 2019 (COVID-19) has resulted in an increase in known risk factors for mental health problems. Mexico adopted lockdown and physical distancing as a containment strategy with potential consequences on day to day life, such as social isolation, loss of income and loneliness that can have important consequences in terms of mental health. Objective. We aimed to examine the effect of the initial phases of the COVID-19 pandemic on psychological distress, well-being and perceived physical health among Mexican-base respondents and to examine whether coping strategies would play a potential intermediating role in relation to these variables. Under the Existential Positive Psychology perspective, an emphasis was made on meaning-centered coping. Methods. A cross-sectional study was conducted between April 30 and June 16th 2020 among 604 Mexicans-base respondents of which 471 were women and 132 men. Data was collected by using online questionnaires. Psychological distress was measured using the Depression, Anxiety and Stress Scale (DASS-21). The Brief COPE Inventory was used to assess problem-focused and emotion-focused coping strategies. We also used the Meaning-Centered Coping Scale (MCCS). PERMA was used to assess well-being, perceived physical health, and loneliness. Profiler and Descriptive analysis and bivariate linear regression were performed to examine the association of variables. Results. 45.9% of the participants reported moderate to extremely severe psychological distress. Our results demonstrate that problem-focused and emotion-focused coping were positively related to psychological distress, whereas meaning-centered coping was negatively associated with distress. Furthermore, psychological distress played a potential negative role in the perceived physical health, while meaning-centered coping and well-being buffered the negative influence of psychological distress on perceived physical health (completely standardized indirect effect = -0.01, SE: 0.012, 95% CI [- 0.065; - 0.017]. Conclusion. Meaning-centered coping and subjective well-being act as buffers of psychological distress in the COVID-19 pandemic. Future studies can further examine the value of the critical role of meaning in life in promoting well-being as a protective factor against severe distress during traumatic events.